The Influence of Environmental Effects on Type Ia Supernovae Standardization - Baluta, A. Yu.; Pruzhinskaya, M. V.; Rosnet, P.; Pauna, N.
Type Ia Supernovae (SNe Ia) are used as reliable cosmic distance indicators and their standardization is necessary for a more accurate measurement of the cosmological parameters of the Universe using the Hubble diagram. However, the Hubble diagram still shows intrinsic dispersion, potentially influenced by the supernova’s environment. In this study, we reproduce Hubble fit diagrams for the Pantheon supernovae data, and also investigate the possibility of introducing various standardization equations for supernovae that exploded in early- and late-type galaxies. We analyze 330 SNe Ia from the Pantheon cosmological sample to study how host galaxy morphology affects SN Ia standardization. We find that SNe Ia hosted by early-type galaxies have different standardization parameters compared to those hosted by late-type galaxies. We conclude that correcting for host galaxy morphology significantly impacts the accuracy of the Hubble diagram fit.
Keywords: Astrometry; Space Sciences; Archaeoastronomy and Astronomy in Culture